The efects of cooperative learning strategies to develop fluency in 9th grade students at Guillermo Cano National institute in the first school term, 2019 - Herrera Godoy, Judith Adalgitce | Arosteguí Irías, Norman Ulises | Rodríguez López, Judith Bernavelia | Espinoza Barahona, Jeydels Alexander Espinoza Barahona Jeydels Alexander (Nicaragua | ESTELI UNAN-Managua, FAREM-Estelí, Nicaragua, 2019)
This study is focused on the importance of implementing cooperative learning strategies for; developing fluency of the English language on 9th grade students at Guillermo Cano; National Institute. Therefore researchers formulated two main questions based on research; objectives to guide it: What type of cooperative learning strategies should be applied for; students to develop fluency in the English class? How do cooperative learning strategies; contribute to develop the students´ fluency? This research follows a qualitative design and; aims at presenting new strategies that will be useful for English teachers and productive for; students. We identified which strategies are the most effective in the English class and can be applied; by English teacher in Nicaraguan classrooms. Firstly, students of 9th grade can develop; better communication through fluency with the implementation of cooperative learning in; the learning process. Secondly, students' performance improved significantly and they; developed good attitude toward learning English via cooperative learning. Thirdly, when; using cooperative learning students are motivated and less reluctant. Therefore, this study; recommends the adoption of cooperative learning as a strategy fluency development in; English Learning speaking in particular.
Seminario-(Licenciados en Ciencias de la Educación con mención en Inglés)-Universidad Nacional Autónoma de Nicaragua
Keywords: Inglés básico enseñanza | Aprendizaje cooperativo | Enseñanza-Inglés | Estrategias de aprendizaje | Inglés-Seminario-2019 | Lectura oral